Cutaneous horn in a sun-protected site harbouring unusual malignancy - Ramji, Ashwath Narayan (International Surgery Journal, 2019)
Cutaneous horns are conical, circumscribed projections formed by desquamation and layering of keratin. Although they can appear on the skin anywhere on the body, they are most commonly seen on the sun-exposed surfaces, and are often associated with solar keratosis. Cutaneous horns are most often benign, however they are a potential site of malignancy and may harbor premalignant or malignant lesions, the most common being squamous cell carcinoma, the causal relationship being straightforward and both squamous cell carcinoma and cutaneous horns can be equated with the common epithelial maker keratin. Other histological types of malignancies are not usually noted in conjunction with cutaneous horns. Here we describe a patient with a cutaneous horn over the volar aspect of the right forearm, a sun-protected site, harboring basal cell carcinoma, an infrequent finding.